Game-based physical education learning to improve basic manipulative movement skills in primary school children - Satria, M. Haris; Aliriad, Hilmy; Nuzulia, Dian; Mangngassai, Ince Abdul Muhaemin; Junaidi, Ilham Arvan; Zainuddin, Moh. (Edelweiss Applied Science and Technology, 2024)
Physical education plays an important role in the development of children's motor skills, especially at primary school age. Basic manipulative movement exercises that focus on object manipulation, ball games and other games can accelerate the development of hand-eye coordination and gross motor skills. This study aims to develop and implement an effective game-based physical education learning model to improve the basic manipulative movement skills of primary school children. The type of research used is pre-experimental research, one group pre-test post-test design. The study population consisted of students aged 9-10 years of grade 4 in Palembang City, with a sample of grade 4A total 25 students who participated in game-based learning for 8 sessions. The results of this study indicate that the use of the game model in learning has a significant effect on the improvement of learners' manipulative movement skills. Educators and coaches are advised to use the game model as the main tool in children's motor development, with adaptations based on learners' initial abilities.